ANXIETY AND ACCEPTANCE OF GRIEF IN PREGNANT WOMEN WHO HAVE TERMINATED PREGNANCY - Darmayasa, I Made; Sitanggang, Amita Rouli Purnama (JURNAL KESEHATAN REPRODUKSI, 2024)
Background: Termination of pregnancy is a major life event and can even be a traumatic experience. A woman who undergoes a termination of pregnancy loses not only her fetus but also her dreams and plans for her child. This can cause disturbances in a person's psychology, and one of them is in the form of anxiety.Objective: To study and determine the anxiety and acceptance of grief in pregnant women who are about to terminate their pregnancy.Method: Serial case reports of two cases of pregnant women with congenital abnormalities who are about to terminate their pregnancy. Interviews were conducted at the Obstetrics and Gynecology Polyclinic at Prof. Dr. I. G. N. G. Ngoerah General Hospital Denpasar related to the mental condition experienced before the termination of pregnancy and how the social support received by the patient. Both anxiety measurements were carried out using the Beck Anxiety Inventory (BAI) and Hamilton Anxiety Rating Scale (HARS) questionnaires.Results and Discussion: The two pregnant women with termination plans at the Obstetrics and Gynecology Polyclinic at Prof. Dr. I. G. N. G. Ngoerah General Hospital Denpasar experiences anxiety although it cannot be categorized as severe anxiety. In facing termination, the two patients also experienced difficulties in accepting grief which improved along with the provision of education and assistance from the medical team. For clients and families, the experience of abortion can be a separate stressor that is very influential both physically and psychologically for the client. The choice to undergo termination of pregnancy (both voluntary and therapeutic) is highly personal and complex for the woman and her partner because many factors are involved in the decision-making process. Performing therapeutic termination of pregnancy is very personal and several demographic and reproductive factors can contribute. Women who undergo termination of pregnancy have a higher risk of developing mental disorders.Conclusion: Termination of pregnancy is a difficult process. This process can cause several mental disorders such as anxiety disorders in pregnant women who are about to terminate. In the decision-making process, the pregnancy termination team must consider all aspects, both psychological and cultural, that are adhered to by the patient.